EFFECT OF ASPIRIN ON FERTILITY OF MALE WHITE MICE - Ihsan R.Ibrheem; Adnan S.AL-Janaby (University of Thi-Qar Journal of Science, 2019)
Thirty mice males were divided into three groups.First group was injected with (50 mg/kg) of aspirin,the second was injected with(150 mg/kg)and the third group termed as control group and injected with distiled water.The experiment continued for four weeks .In the end of the experiment half of males were mated with untreated females.The number and weight of litters were recorderd in addition to the length of gestation .The second half of males were anesthetized, then epididymis was removed.The total sperm count,the percentage of live and dead sperms and the percentage of motile and non-motile were counted .The results showed that there was a significant decrease(p<0.05) in the litters number and significant increase(p<0.05) in the period of pregnancy .Also there was a significant decrease(P<0.01) in the percentage of live and motile sperms in the both groups compared with control group .Also the percentage of dead and non-motile sperms were increased significantly(P<0.01)in both groups compared with control group. These effects of aspirin maybe due to the action of aspirin as prostagland inhibitor.